FGF2/EGF contributes to brain neuroepithelial precursor proliferation and neurogenesis in rat embryos: the involvement of embryonic cerebrospinal fluid. Issue 1 (9th December 2019) - Lamus, F.; Martín, C.; Carnicero, E.; Moro, J.A.; Fernández, J.M.F.; Mano, A.; Gato, Á.; Alonso, M.I.
Abstract: Background: At the earliest stages of brain development, the neuroepithelium works as an interdependent functional entity together with cerebrospinal fluid, which plays a key regulatory role in neuroepithelial cell survival, replication and neurogenesis; however, the underlying mechanism remains unknown in mammals. Results: We show the presence of fibroblast growth factor 2 (FGF2) and epidermal growth factor (EGF), in 13.5‐day rat embryo cerebrospinal fluid (eCSF). Immunohistochemical detection of FGF2 expression localized this factor inside neuroepithelial precursors close to the neuroepithelial‐CSF interface, suggesting that FGF2 from eCSF could originate in the neuroepithelium by apical secretion. The colocalization of FGFR1 and FGF2 in some neuroepithelial cells close to the ventricular surface suggests they are target cells for eCSF FGF2. Brain neuroepithelium EGF expression was negative. By using a neuroepithelial organotypic culture, we demonstrate that FGF2 and EGF from eCSF plays a specific role in triggering the self‐renewal and are involved in neurogenetic induction of mesencephalic neuroepithelial precursor cells during rat development. Conclusions: We propose eCSF as an intercommunication medium for neuroepithelial precursor behavior control during early rat brain development, and the neuroepithelial regulation of FGF2 and EGF presence in eCSF, as a regulative mechanism controlling precursor proliferation and neurogenesis. Key Findings: We show the presence of Fibroblast Growth Factor (FGF2 and EGF) in 13.5‐day rat embryos cerebro‐spinal fluid (eCSF). FGF2 expression localized this factor at the apical end of the neuroepithelial precursors in contact with eCSF. We demonstrate that FGF2/EGF from eCSF plays a specific role in triggering replication and in neurogenesis induction of neuropeithelial cells. We propose eCSF as a common phylogenetical factor in neuroepithelial precursor behavior during rat brain development.